Usefulness of traditional and new performance measures: Some evidence from Singapore companies - KHOO, Teng Aun (Institutional Knowledge at Singapore Management University, 1994)
This paper reported the findings of a survey study on the usefulness of selected traditional and new performance measures used by Singapore companies that have adopted a flexible manufacturing strategy. The results indicated that the majority of these companies considered the new performance measures useful particularly among the larger companies and among those with 5 years or less of business experience. Traditional measures are still useful, though to a much lesser extent. These results suggested that a combination of both traditional and new measures would be needed especially when Singapore companies are going through the transition of implementing changes to their strategies from cost leadership to flexible manufacturing.